Volumetric and Linear Adaptation of an Indirect Adhesive Restoration: Comparison of Chairside 3D Printing and Milling Techniques - Andrea Baldi; Tommaso Rossi; Ilaria Stura; Allegra Comba; Mauro Fazioni; Chiara Rolando; Giorgio Ferrero; Paola Ceruti; Nicola Scotti (Applied Sciences)
The aim of this study was to the evaluate volumetric and linear adaptation of an indirect adhesive restoration, comparing a novel chairside 3D printer to conventional milling techniques. An intact upper premolar was selected, prepared for an overlay restoration, and replicated. A standardized overlay restoration was designed with CAD software (Cerec inLab CAD SW 4.5.2, Dentsply Sirona, Charlotte, NC, USA), maintaining equal morphology for each sample. Restorations were produced with three CAM processes: chairside 3D printer (D-FAB, DWS, Thiene, Italy), chairside milling unit (Cerec MCXL, Dentsply Sirona, Charlotte, NC, USA), and an industrial milling machine serving as control (Micro 5x, Aman Girrbach, Mäder, Austria). Once cemented, specimens were scanned using micro-computed tomography to assess volumetric, internal, and external adaptation. Data were statistically analyzed with ANOVA and post hoc Bonferroni tests. CAM technique significantly affected volumetric adaptation (p < 0.001), with the chairside 3D printer performing the best and chairside milling unit the worst. Concerning internal adaptation, the chairside milling unit performed significantly worse than the other groups (p < 0.001). No significant differences were reported for external adaptation (p > 0.05). In conclusion, CAM technique influenced volumetric and internal adaptation, with the 3D printer showing optimal volumetric adaptation and chairside milling poor internal adaptation.